2017
DOI: 10.3847/1538-4357/aa6d7d
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Solar Coronal Rotation

Abstract: In this paper, by applying the wavelet transformation analysis to the data of the daily 10.7 cm radio flux covering the period from 1947 February 14 to 2014 August 31, a significant period of about 27 days can be found, indicating the existence of rotational modulation in the temporal variation of the daily 10.7 cm radio flux. Then, the solar coronal rotation periods are obtained based on the result of the wavelet transformation analysis, and the temporal variation of the coronal rotation is revisited. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 63 publications
7
30
0
Order By: Relevance
“…It is clear from Figure 9 that the long-term decreasing trend of PLRC time series we obtained is similar to those obtained by Heristchi & Mouradian (2009), , Li et al (2012), and Xie et al (2017b). Interestingly, all of these studies used the daily 10.7 cm solar radio flux to reveal the rotational behavior of the solar corona.…”
Section: Temporal Variation Of Coronal Rotationsupporting
confidence: 77%
See 4 more Smart Citations
“…It is clear from Figure 9 that the long-term decreasing trend of PLRC time series we obtained is similar to those obtained by Heristchi & Mouradian (2009), , Li et al (2012), and Xie et al (2017b). Interestingly, all of these studies used the daily 10.7 cm solar radio flux to reveal the rotational behavior of the solar corona.…”
Section: Temporal Variation Of Coronal Rotationsupporting
confidence: 77%
“…Most recently. by studying the temporal variation of coronal rotation in the 10.7 cm radio flux, Xie et al (2017b) found a periodicity of 6.6 years, which was interpreted as the third harmonic of the 22-year magnetic cycle. A similar periodicity of 6.8 years was found by Xie et al (2018) who studied the equatorial rotation rate of solar magnetic fields from 1975 September to 2008 April.…”
Section: Periodicity In the Plcr Time Seriesmentioning
confidence: 99%
See 3 more Smart Citations